The Effect of Patch Size on Morphology and Growth on The Intertidal Box Mussel Septifer bilocularis L., in North Sulawesi, Indonesia - Medy Ompi; Lawrence J.L. Lumingas (Jurnal Moluska Indonesia, 2019)
Isolated small and large patches of Septifer bilocularis were divided into three length size classes: small (>10 to 17 mm), medium (>17 to 23 mm), and large (>23 mm) mussels. Each group was divided into three groups of different densities to form isolated patches (10 individuals), medium patches (50 individuals), and large patches (100 individuals). Three replicates of each patch size were established. Each density group was placed in a cage and returned to their natural hard bottom substrata, placed randomly, 50 cm between cages. At low water level, the area was exposed to air. The length / weight regression line of mussels in small and large patches overlapped, but there was a significant difference between the slopes (ANCOVA, p<0.05). Mussels occurring in small patches were heavier and thicker than those of larger patches. Box mussels in small patches had significantly higher growth than mussels in medium and large patches